Livsformer og livskvalitet i Grønland:Et indblik i sammenhængen og den potentielle udvikling - Steenholdt, Naja Carina (Politik, 2019)
This article examines how life modes and quality of life are related in Greenland from a social science perspective. The article also relates to how this is linked to the country's development towards independence. Quality of life and the notion of the good life belong to the cultural and value-laden aspects of ways of life. In other words, it is a notion of how things should, must or may be, in order for us to feel that life is good. But the physical locality of where a person lives is also important. It is a classical notion that people have substantially different ways of life in a city versus a settlement, and that values and attitudes to what quality of life can be, substantially varies between the two. Based on the results of a quality of life studies in South Greenland in 2018 and through an analysis and discussion of Thomas Højrups’ life mode analysis, the article seeks to answer the following questions: How are life modes and quality of life in Greenland interrelated? And how are they linked to the current development towards independence? The article argues that life modes and quality of life are to a large extent associated with relations to family, nature and work, but that the ability of the Greenlandic people to adapt also plays a role in the relationship between life forms and quality of life